Evaluation of Post-harvest Quality of Marigold Flowers After Packaging and Storage in Different Seasons (Bangladesh Journal of Botany, 2022)
In the present study, the keeping quality of differently packed and stored marigold flowers was evaluated under ambient conditions during summer and rainy seasons. The shelf life of marigold was 1 day in summer and 4 days in rainy season which was supported by high membrane stability index, relative water content, total soluble proteins, total soluble sugars, lesser loss in physiological weight, minimum spoilage and maximum freshness index of flowers in rainy season. The ice box, CFB box and polythene packages showed better results in comparison to gunny bag and onion mesh bag. One day storage was better in comparison to two and three days in all the seasons. Thus, marigold flowers can be packed in ice box, CFB box and polythene for 2 to 3 days without any adverse effect on keeping quality during rainy season.Bangladesh J. Bot. 51(2): 247-254, 2022 (June)